Effect of pH value on adsorption of Levofloxacin in agricultural silty clay of North China. Issue 2 (April 2020) - Wei, M X; Lv, D Y; Cao, L H; Yang, H Y; Jiang, K
Abstract: The entry of quinolone antibiotics into the soil will cause serious soil antibiotic contamination. The migration and whereabouts of antibiotics in soil are mainly affected by soil adsorption. The change of pH value will have a great impact on soil adsorption. In this paper, the adsorption characteristics of typical fluoroquinolones (levofloxacin) in the silty clay widely distributed in the farmland of North China and the effect of pH value change were studied. The results show that Langmuir adsorption isotherm model can well fit the isotherm adsorption process of levofloxacin on silty clay. The adsorption process of levofloxacin on silty clay was fast, and equilibrium was reached in about 16 hours. The adsorption amount decreases with the increase of pH value. After the pH value reaches 10.86, the adsorption amount rises.